Κριτικὴ Ἀποκατάσταση καὶ χρήση τοῦ Α΄ Τιμ. 3:6 στοὺς ἱεροὺς κανόνες, (Critical Restoration and use of 1 Tim 3:6 within the Holy Canons) ([Νομοκανονική Βιβλιοθήκη 24], Ἐπέκτασις, 2009)
The 2nd Canon of the 1st Ecumenical Synod, reads he 1 Tim 3:6 with the word "trap"῾ before the phrase "of the devil". An hermeneutical "deadlock" is now solved.The Canon is a credible "external witness" of the authentic biblical text. In the critical restoration of the holy text we follow the holisitc-rational approach. The real meaning of the particular verse, which is an excerpt of the Holy Scripture is revealed by an equally ῾holy῾ text, the second canon of the First Ecumenical Synod. Apart from the critical restoration, it is noted that the canon "repeats" 1 Tim 3:6 in order to introduce to the canonical corpus of the Church the prohibition of ordination of the recently baptised. We watch the canonical evolution of this prohibition, comparing this first canon with later canonical regulations, as well as, the semantic evolution of the word "neophytus" (=recently baptised). The word is recognized as terminus technicus in canon law, which includes every person who has recently abandoned secular life wishing to be ordained, or a recently ordained clergyman, which is not mature enough to ascend the hierarchy. We observe, that through time penal provisions become more lenient, however the categories of the subjects which are included in the ban expands.